2022
DOI: 10.31557/apjcp.2022.23.12.4063
|View full text |Cite
|
Sign up to set email alerts
|

Development of PEGylated PLGA Nanoparticles Co-Loaded with Bioactive Compounds: Potential Anticancer Effect on Breast Cancer Cell Lines

Abstract: Objective:The incidence of breast cancer continues to rise despite decades of laboratory, epidemiological and clinical research. Breast cancer is still the leading cause of cancer death in women. Cyclin D1 is one of the most important oncoproteins associated with cancer cell proliferation and is overexpressed in more than 50% of cases. Curcumin and chrysin are plant-derived components that are believed to assist in inhibiting the viability of breast cancer cells. These agents are involved in cancer cells' grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…It suggests that by improving MET’s and SIL’s solubility and bioavailability, this form of drug delivery system could enhance its transport to cancer cells ( 48 ). The findings of our investigation are in agreement with those of former research that has shown that MET and SIL inhibit the growth and proliferation of the A549 cell line ( 52 54 ).…”
Section: Resultssupporting
confidence: 93%
“…It suggests that by improving MET’s and SIL’s solubility and bioavailability, this form of drug delivery system could enhance its transport to cancer cells ( 48 ). The findings of our investigation are in agreement with those of former research that has shown that MET and SIL inhibit the growth and proliferation of the A549 cell line ( 52 54 ).…”
Section: Resultssupporting
confidence: 93%
“…In vivo, studies with human leukemia 60 (HL-60) cells report that concentrations between 20 and 30 µM are sufficient to exert an inhibitory effect on cytosolic PKC activity and membrane tyrosine protein kinase (TPK) activity. Within the same study, it is noted that a concentration of 80 µM is sufficient to block the activity of phosphatidylinositol (4,5) bisphosphate [75]. On the other hand, it has been shown that quercetin induces the inactivation of the AKT protein, an antiapoptotic protein, by decreasing its phosphorylation and also directly inactivates procaspase 9, thus blocking Another pathway susceptible to quercetin action is the protein kinase C (PKC) pathway, which is also downregulated [73]; by blocking the diacylglycerol (DAG) precursor of PKC, inhibition of this pathway leads to blocking the formation of phosphatidylinositol (3,4,5)trisphosphate, which activates the entry of extracellular calcium [74].…”
Section: Cancermentioning
confidence: 84%
“…In vivo, studies with human leukemia 60 (HL-60) cells report that concentrations between 20 and 30 µM are sufficient to exert an inhibitory effect on cytosolic PKC activity and membrane tyrosine protein kinase (TPK) activity. Within the same study, it is noted that a concentration of 80 µM is sufficient to block the activity of phosphatidylinositol (4,5) bisphosphate [ 75 ]. On the other hand, it has been shown that quercetin induces the inactivation of the AKT protein, an antiapoptotic protein, by decreasing its phosphorylation and also directly inactivates procaspase 9, thus blocking cellular apoptosis [ 76 ].…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…CD44 is closely related to the growth, infiltration, and metastasis of tumors, thereby inducing cell apoptosis. Functional PLGA drug delivery systems can also improve the inhibition of the proliferation of Caco-2 cells by regulating their cell cycles ( Luo et al, 2019 ; Moghaddam et al, 2021 ; Mohammadinejad et al, 2022 ). PLGA can release drugs in vivo and in vitro through mechanisms such as degradation into water-soluble lactic acid and glycolic acid, and surface erosion, thereby changing the cell environment and affecting the cell cycle.…”
Section: Resultsmentioning
confidence: 99%